2009
DOI: 10.1093/schbul/sbp015
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Model of Cognitive Insight in First-Episode Psychosis: Verbal Memory and Hippocampal Structure

Abstract: Our previous work has linked verbal learning and memory with cognitive insight, but not clinical insight, in individuals with a first-episode psychosis (FEP). The current study reassessed the neurocognitive basis of cognitive and clinical insight and explored their neural basis in 61 FEP patients. Cognitive insight was measured with the Beck Cognitive Insight Scale (BCIS) and clinical insight with the Scale to assess Unawareness of Mental Disorder (SUMD). Global measures for 7 domains of cognition were examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
47
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 65 publications
7
47
2
Order By: Relevance
“…21 A second study by this group largely corroborated these findings, with the exception that Self-Reflectiveness (rather than Self-Certainty) correlated with verbal memory. 29 This last study was also the first to report brain imaging results. Specifically, a smaller overall hippocampal volume was associated with higher Self-Certainty, and reduced left-hemisphere hippocampal volume also correlated with a lower Composite Index score.…”
Section: Functional Outcomementioning
confidence: 91%
See 4 more Smart Citations
“…21 A second study by this group largely corroborated these findings, with the exception that Self-Reflectiveness (rather than Self-Certainty) correlated with verbal memory. 29 This last study was also the first to report brain imaging results. Specifically, a smaller overall hippocampal volume was associated with higher Self-Certainty, and reduced left-hemisphere hippocampal volume also correlated with a lower Composite Index score.…”
Section: Functional Outcomementioning
confidence: 91%
“…11,12,16,17 However, 2 studies have reported partially contrary findings: In each case, higher Self-Reflectiveness (but not Self-Certainty) was associated with depression in psychotic patients. 20,24 Two studies have investigated the association between anxiety and cognitive insight in psychosis, and the results are similar to depression, with one group finding no significant associations 29 and the other finding significant positive correlations between anxiety and both the Composite Index and SelfReflectiveness. 20 …”
Section: Depression and Anxietymentioning
confidence: 95%
See 3 more Smart Citations